Interactions of the CSF3R polymorphism and early stress on future orientation: evidence for the differential model of stress-related growth - Yiqun Gan; Lizhong Wang; Yidi Chen; Lei Zheng; Xiaoli Wu; Gang Chen; Yueqin Hu (Epidemiology and Psychiatric Sciences)
Abstract Aims This study aims to explore the concept of future orientation, which encompasses individuals’ thoughts about the future, goal-setting, planning, response to challenges and behavioural adjustments in evolving situations. Often viewed as a psychological resource, future orientation is believed to be developed from psychological resilience. The study investigates the curvilinear relationship between childhood maltreatment and future orientation while examining the moderating effects of genotype.